Self-Reported and Objectively Measured Physical Activity of Elderly Womens From Bar and Podgorica - Marko Knezevic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
Physical activity as a way of living has a big impact on health, physical and psychic development of a man. There is a wrong belief that by being a sportsman and physical active, implies that one does all these things on the highest level. On the other hand, the real truth is that a small number can achieve something on a professional level, the ones who are physically active as recreational, are much more numerous. We did this research in order to find out how physically active are people from the third age. We used a standardized IPAQ questionnaire in order to get precise results, and we tried to establish the level of physical activity at work, transport, house works and in their free time. A sample of 100 respondents aged from 50 to 69 years, from Bar and Podgorica, was divided into two subsamples. One subsample with 39 respondents aged from 50 to 59 years, and the other subsample with 61 respondents aged from 60 to 69 years. The results of the research have shown that a low level of physical activity in transport have the respondents of the older group (333.58 MET). The same level of activity is present for both groups in free time activities, for younger group 566,61, and for the older group 512,36. Moderate physical activities are present with the younger group in transport physical activities (614,82). All the other ways of physical activity are present with both groups on a high level. By comparing these two subsamples with a t-test (level of significance 0,01), it has been established that there is a statistically significant difference between the results of total activities in transport, total activities in house work, total walking, total moderate intensity activities and total work.